EVALUASI PERENCANAAN ATAS PAJAK PENGHASILAN (PPH) PASAL 21 SEBAGAI UPAYA MEMINIMALKAN BIAYA PAJAK PADA PT GRAHA POWER ENERGY - Budi Tri Rahardjo (Jurnal Manajemen Bisnis Krisnadwipayana, 2017)
The purpose of this study is to know the tax planning undertaken by the company is appropriate and in accordance with the applicable tax laws in an effort to minimize the taxation terutangnya. The research method used is descriptive analysis method. The object of research used is evaluation of planning on Income Tax (PPh) Article 21. This research evaluate planning of Income Tax (PPh) Article 21 as an effort to minimize tax cost. The results achieved are having a considerable impact on the company's activities. The owner of the company would want to enjoy the results of his business to the fullest. Therefore it is necessary to prepare a tax planning coordinated with long-term plans and short-term plans of the company. The conclusion is that the difference that occurs after applying the tax planning is a tax savings that can be obtained by the company. Where before the implementation of tax planning, income tax to be paid company is Rp. 425,671,743.25 and seteah doing tax planning to Rp. 341,456,597.75. So obtained tax savings of Rp. 84,215,145.50 the difference can be used by the company for something more useful and useful.